Students’ learning autonomy, involvement and motivation towards their English proficiency - Yen Hoang Phuong; Phuong Quyen Vo (EduLite: Journal of English Education, Literature and Culture, 2019)
Different factors are involved in the process of learners’ learning English as a second or foreign language. Among them, learning autonomy, involvement and motivation and attitude toward English language learning have been claimed to positively correlate with learners’ English proficiency. In the current study, 229 English-majored final-year students at a university in Vietnam were invited to participate in a survey to explore their English proficiency level and factors that may have impacted that level. Findings revealed that students’ learning autonomy and their active participation in classroom activities are the most influential on their English proficiency level after four years of learning. As a result, the study suggests that measures should be taken to improve students’ learning autonomy and classroom involvement.